Effectiveness of a relaxation intervention (progressive muscle relaxation and guided imagery techniques) to reduce anxiety and improve mood of parents of hospitalized children with malignancies: A randomized controlled trial in Republic of Cyprus and Greece - Tsitsi, Theologia; Charalambous, Andreas; Papastavrou, Evridiki; Raftopoulos, Vasilios (My University, 2017)
Purpose To explore the effect of Progressive Muscle Relaxation (PMR) and Guided Imagery (GI),in reducing anxiety levels among parents of children diagnosed with any type of malignancy receiving active treatment at a Paediatric Oncology Unit in Republic of Cyprus and in Greece. Method A randomized non-blinded control trial was conducted between April 2012 to October 2013, at two public paediatric hospitals. Fifty four eligible parents of children hospitalized with a malignancy were randomly assigned to the intervention (PMR and GI) (n = 29) and a control group (n = 25). The study evaluated the changes in anxiety levels(HAM-A) and mood changes(POMSb). Results There was a statistically significant difference in the mean scores of the subjects in the intervention group in HAM-A scale between the T0 (14.67 ± 9.93) and T1 (11.70 ± 8.15) measurements (p = 0.008) compared to the control group in which a borderline difference (16.00 ± 11.52 vs 13.33 ± 8.38) was found (p = 0.066). The effect size for the intervention group was low to moderate (0.37). Regarding mood changes, there was a statistically significant difference in tension for parents in the intervention group between T0 and T1 (11.15 ± 5.39 vs 9.78 ± 4.26), (p = 0.027). Furthermore, the parents in the intervention group were significantly less sad following the intervention (T1) (2.81 ± 1.07 vs 2.19 ± 1.21), (p = 0.001), and felt significantly less tense (2.93 ± 0.91 vs 2.26 ± 0.90), (p = 0.001) and anxiety (2.63 ± 1.21 vs 2.19 ± 1.07), (p = 0.031) compared to those in the control group. Conclusions These findings provided evidence on the positive effect of the combination of PMR and GI in reducing anxiety and improving mood states in parents of children with malignancy.
Keywords: Neoplasms; Child; Adult survivors